Pesan-Pesan Akhlak Dalam Program Siaran Dakwah Pemuda Hijrah Radio Fajri 99.3 Fm Bogor Tahun 2019 - Iskandar Muda Harahap; Muhammad Nur Kholis AR (Journal on Education, 2023)
Every mu’min is required to have a good character where the character is reflected in the deeds in his daily life. The Prophet must be used as a guide in behavior, because God has given a great character inside the Prophet as an example for all humanity. Radio is an effective mass media that can be used as a medium for delivering Islamic da'wah messages to the public. One of the advantages of preaching through radio is that it does not require a large fee, where the message of preaching can also be conveyed quickly. Since the beginning until now, Radio Fajri 99.3 FM continues to be consistent in delivering da'wah. Many kinds of broadcast/rubric material are provided by this radio for loyal listeners. Based on the above context, the purpose of this study was to find out what moral messages contained in the Pemuda Hijrah Da'wah Broadcats Program of Fajri Radio 99.3 FM Bogor in 2019 and the relationship between moral messages in the Pemuda Hijrah Da'wah Broadcats Program of Fajri Radio 99.3 FM Bogor in 2019 with the characteristics of human spiritual intelligence The method used in this research was the content analysis method with a descriptive qualitative approach. Data collection was carried out using observation and documentation techniques, namely by collecting recordings of all episodes of the Pemuda Hijrah Da'wah Broadcast Program in 2019. The population of this study was 150 audio recordings (150 episodes). Then the researcher used a purposive sampling method in determining the sample where the sample size was about 10% of the population which was as many as 16 episodes. From the results of this study it can be concluded that the moral messages in the Pemuda Hijrah Da'wah Broadcast Program of Fajri Radio 99.3 FM Bogor in 2019 are patience, trust, devotion to parents (birrul walidain), piety, honesty, gratitude, sincerity, and qana’ah. The relationship between moral messages in Pemuda Hijrah Da'wah Broadcast Program of Fajri Radio 99.3 FM Bogor in 2019 with the characteristics of human intelligence is very close. Every feature of human spiritual intelligence is related to the teachings of Islamic morals. The first characteristic describes the character of trust, the second character describes the character of piety, the third character describes the character of self-introspection (muhasabah), the fourth character describes the character of patience, the fifth character describes the firm character of the establishment (tsabat), the sixth character describes the honest character, the seventh character describes the morality of qana'ah, and the eighth character describes sincerity.